Genetic parameters of survival for six generations in the giant freshwater prawn Macrobrachium rosenbergii. (13th September 2013) - Luan, Sheng; Wang, Junyi; Yang, Guoliang; Luo, Kun; Chen, Xuefeng; Gao, Qiang; Hu, Honglang; Kong, Jie
Summary: Genetic parameters were estimated for survival of Macrobrachium rosenbergii using a fully pedigreed synthetic population formed by three introduced strains. The data included 107 398 progeny from 394 sires and 654 dams in six generations with a nested mating structure. The variance components and genetic parameters were estimated using a generalized linear mixed model with the probit link function. Available heritabilities in survival from the generation G3 to G5 ranged from 0.007 ± 0.020 to 0.066 ± 0.044 ( P  >   0.05) using a model that included the common environmental effect (c). Across generations, low heritability (0.016 ± 0.012, P  >   0.05) was estimated using the model with inclusion of the c effect. There were statistically significant differences in the heritability estimates between different ponds for most generations. Moreover, the genetic correlation of survival between ponds over six generations varied from low to high (−0.0007 ± 0.17 to 0.80 ± 0.069) and was significantly different from unity. There were low correlation coefficients (−0.039 ± 0.096 to 0.342 ± 0.081) between body weight estimated breeding value (EBV) and survival EBV of families in different generations. The low heritabilities for survival are most likely caused by low genetic variation in the founder populations and reduced genetic variation because of consecutive selection.